The Relationship between Self-Compassion and Prosocial Behavior in Late Adolescents in DKI Jakarta - Putri Amara, Keisha; Bellarosa Yosza, Amearah; Lamria Lisbet Naibaho, Naomi (Lafadz Jaya Publisher, 2024)
This study aims to determine the relationship between self-compassion and prosocial behavior in late adolescents in DKI Jakarta. The researcher employed a quantitative approach and utilized purposive sampling to select 400 subjects aged 18-21 years who lived in DKI Jakarta. Data were collected using the Prosocial Behavior Scale (PBS) and the Self-Compassion Scale (SCS). The data processing involved hypothesis testing through the Pearson correlation test. The results revealed a significant positive relationship between self-compassion and prosocial behavior, with a correlation coefficient of r = 0.107 and a p-value of 0.032, which is less than the significance level of 0.05. These findings suggest that higher levels of self-compassion are associated with greater prosocial behavior in late adolescents in this region. This research highlights the importance of fostering self-compassion as a potential means to enhance prosocial behavior among adolescents. Given the cultural context of DKI Jakarta, where communal values and social harmony are emphasized, self-compassion may play a crucial role in promoting positive social interactions and behaviors. Future studies could further explore the underlying mechanisms of this relationship and consider interventions to cultivate self-compassion in adolescents to support their social development and well-being.